“HUMANITY” ASPECT OF EVENTUAL USE OF THE NEUTRON WEAPONS (Annual of the Faculty of Philosophy in Skopje, 2020)
The non-proliferation of nuclear weapons is a matter of policy and social responsibilityfor world peace, while the peaceful development of nuclear technology is amatter of freedom, sovereignty and equality of nations. It is known that the improvementand development of nuclear weapons in the Cold War era was a constant process.In this paper, the author addresses the reasons behind the development and introductionof certain types of nuclear weapons in the armament, which according to the developmentprograms at that time it is classified as weapons with intensive initial nuclearradiation. The neutron weapons emerge in part as a consequence of the doctrines ofnuclear countries in accordance with the classification of possible wars that would havetaken place in that era. The logical consequence of such a situation was the limited nuclearwar, in which the nuclear forces became not only the owners of nuclear weapons,but also its hostages. The vision was that in a match with limited nuclear strikes, thewinner might be the side that has more sophisticated weapons at the moment. The neutronbomb, officially defined as a high-radiation weapon, is a low-performance thermonuclearweapon designed to maximize deadly neutron radiation in the immediate vicinityof an explosion while minimizing the physical power of the explosion itself. Thequestion remains whether the spread of various and even partially inaccurate informationthat protection is very difficult, almost impossible, may have one additional motivefor the production and spread of this weapon – to influence morality, the political situationand to exert psychological pressure, not only tо armed forces but also the populationin general ?!
Keywords: NEUTRON WEAPONS; HUMANITY; LIMITED WAR; NUCLEAR ENERGY; RADIATION